PENANGANAN KASUS PELECEHAN SEKSUAL TERHADAP SISWA SMP MELALUI PENDEKATAN BIMBINGAN DAN KONSELING: TANTANGAN DAN STRATEGI - Maya Enggar Siara (Universitas Negeri Malang, 2024)
Sexual harassment against junior high school students is a serious issue that can impact their mental, emotional, and academic well-being. This research aims to explore the challenges in addressing sexual harassment in junior high schools and the counseling strategies that can be used to address this issue. Several solutions have been implemented, such as training for teachers and counselors, strengthening school policies, and empowering students to report harassment cases. However, the success of implementing these solutions is hindered by a lack of resources and interagency coordination. This study uses a qualitative approach with a focus on case studies to deeply understand cases of sexual harassment in junior high schools. Data were collected through observations, documentation, and interviews with students, teachers, counselors, and parents. The results indicate various forms of harassment, student responses, the role of guidance counselors, risk factors, and psychological impacts. From the findings of this research, it can be concluded that counseling approaches have a positive impact on helping sexual harassment victims by providing a safe space, emotional support, coping strategies, and assistance in reporting to authorities. Recommendations include strengthening the role of guidance counselors, comprehensive sexual education, enhancing supervision and school culture, and fostering collaboration with parents. It is hoped that this research will make a significant contribution to protecting the well-being of junior high school students and strengthening the role of counseling in schools.